International migration and the NGOs working in the field of migration in Turkey - Özçetin, Burak; Emre, Perrin Öğün (International migration, 2024)
This study aims to analyse the activities and discourses of the non‐governmental organizations (NGOs) working in the field of migration in Turkey. The research explores how the NGOs frame the issue of migration differently and how they define and comprehend migration, migrants, and refugees. The article discusses whether the NGOs view refugees as subjects needing help, support, and protection or as actors who have rights and must be empowered and argues that there is tension between the two approaches. These points are discussed through a field study, conducted in 2020 (between February and April), comprising in‐depth interviews with representatives of 13 NGOs working in the field of migration. The study points to structural, historical, and conjectural causes and aspects of the weakness of rights‐based attitudes and activities among the NGOs working in the field of migration in Turkey. The article finds out that the actions of the NGOs working in the field of migration are concentrated on the basic needs of refugees, and structural limitations, such as political pressure, political polarization, and capacity problems, push the NGOs to evaluate the issue of migration within relatively narrow frames. The article also stresses the importance of an enabling political and legal environment and a coherent and structured communication strategy to promote a rights‐based migration agenda.